Effects of exercise training on blood pressure in overweight and obese adolescents: A systematic review (Research, Society and Development, 2021)
The aim of this review was to analyze the effects of physical training on the blood pressure of overweight and obese adolescents, searching to identify the magnitude of the effect in relation to the type of training. The present review used PUBMED, SCOPUS, WEB OF SCIENCE, COCHRANE LIBRARY and LILACS as databases. Inclusion criteria were: (1) Randomized Clinical Trials; (2) Overweight and obese adolescents; (3) Minimum 8 weeks of intervention with physical training; (4) pre and post-training blood pressure outcome measures; (5) control group without intervention and keeping their daily habits. The selected studies were analyzed for their methodological quality using the PEDro scale. Eight articles, out of a total of 625, met the inclusion criteria, totaling 249 participants. Three studies used aerobic physical training as an intervention, two used strength training and four studies used a combination of aerobic and strength training to meet their goals. Of the selected works, five showed significant reductions in their blood pressure values after training intervention, especially in SBP. The results suggest that physical training is capable of reducing blood pressure values, regardless of the type, whether it has aerobic characteristics, strength, or a combination of the two. Although blood pressure values tend to show a greater reduction when aerobic training is performed compared to strength training or combined training, the literature lacks consensus on the characteristics of each type of training and the best prescription strategy.